Customer loyalty for retailers’ growth in Bangladesh: do retailer qualities (attributes and awareness) influence satisfaction and loyalty? - Haque, A. K. M. Ahasanul; Chowdhury, Naila Anwar; Hossain Uzir, Md Uzir; Shamsuddoha, Mohammad (Inderscience Enterprises Ltd., 2022)
Customer loyalty is liable for persevering long-term sustenance of organisations in today’s highly competitive business milieu. The present study investigated the various factors affecting customer loyalty towards retailers. Specifically, this study took the initiative to examine the effects of retailer qualities (attribute and awareness) on customer loyalty through the mediating role of customer satisfaction in the light of stimulus-organism response theory. Data were collected through self-administered questionnaires from conveniently selected 270 retail customers in Dhaka, Bangladesh and were analysed through SPSS and CB-SEM tools to test the hypotheses. The results demonstrated that retailer qualities significantly affect customer satisfaction and loyalty, and customer satisfaction was a successful mediator for these relationships. The results will aid marketers in developing marketing strategies for customer loyalty and academically, be an important addition to the literature and extension to SOR theory. The findings will help the researchers in customer loyalty and retailing studies.